KARAKTERISTIK PENGAYAK GETAR DENGAN SUMBER EKSITASI POROS EKSENTRIK - M Bur; Nazaruddin Nazaruddin; A. I Mahyuddin; J Samudra (Mesin, 2000)
Vibrating screen is an equipment used to seperate material according to its particle size. It is usually operated in combination with a crusher. A vibrating screen prototype has been developed. This prototype, called as